Book Review:Greek Alchemy from Late Antiquity to Early Modernity, ed. by E. NICOLAIDIS, Turnhout, Brepols 2018 - DIMITROV, Bozidar (Byzantina Symmeikta, 2019)
Book Review: Greek Alchemy from Late Antiquity to Early Modernity, ed. by E. Nicolaidis, Turnhout, Brepols 2018